Organoleptic Differences of Biscuits Made From Yellow Pumpkin Flour as a Substitution of Wheat Flour - Ege, Kanisius; Adu, Apris A; Aspatria, Utma (Journal of Public Health for Tropical and Coastal Region, 2023)
Introduction: Wheat flour is made from wheat which is a sub-tropical plant that can be grown easily in tropical environment like Indonesia. In response to this, efforts need to be made to find substitutes for wheat flour through increasing local food acceptability to reduce import dependence of wheat. This study aimed to analyze and determine the organoleptic differences of biscuits made from yellow pumpkin flour. Methods: This type of research is experimental with a completely random design consisting of 6 treatments, namely P1 (0% yellow pumpkin flour : 100% wheat flour), P2 (10% yellow pumpkin flour : 90% wheat flour), P3 (20% yellow pumpkin flour : 80% wheat flour), P4 (30% yellow pumpkin flour : 70% wheat flour), P5 (40% yellow pumpkin flour : 60% wheat flour) and P6 (50% yellow pumpkin flour : 50% wheat flour). Data were analyzed using the Kruskal Wallis test with a significance level of 1% and Mann Whitney test. Results: The results showed that the organoleptic value of biscuits with the highest acceptability from the color aspect was at P2 (3,72), aromatic smell at P2 (3,68), taste at P1 (3,76), and texture at P1 (3,52). Conclusion: This study may conclude the potential use of yellow pumpkin flour mixture when preparing wheat-base biscuits. Therefore, import dependency of wheat can be reduced.